Factors Affecting Intention on Whistleblowing with Anonymous Reporting as Moderating Variable - Rizkianti, Khansa Muthia; Purwati, Atiek Sri (International Journal Accounting Tax and Business, 2020)
Abstract ___________________________________________________________________ Purpose – The aim of this study was to determine the effect of personal cost, the seriousness of frauds, and legal protection to whistleblowing intentions on Auditors from The Audit Board of the Republic of Indonesia with anonymous reporting as a moderating variable. Design/methodology/approach – To test the hypothesis, Multiple Regression Analysis and Moderated Regression Analysis are applied to questionnaire survey data from 81 Auditors from The Audit Board of the Republic of Indonesia. Findings – The results revealed that the seriousness of frauds and legal protection has a positive effect on whistleblowing intentions, but personal cost does not negatively affect the whistleblowing intentions. In addition, anonymous reporting does not moderate the influence of the seriousness of frauds, and legal protection to whistleblowing intentions. Reseach limitations/implications – This study provides relevant empirical evidence in explaining the phenomena or factors that influence whistleblowing intentions based on Prosocial Organizational Theory. Originality/value – This study has made a valuable contribution for scholars and relevant institute to understanding factors that affect whistleblowing intention at The Audit Board of the Republic of Indonesia. Keywords: Personal cost, the seriousness of frauds, legal protection, whistleblowing intentions